Prospect of the newly created avenue in Leopoldstadt on the Tabor, which is lined with 400 young fringes, and the old Keyserliche Favorita - Kleiner, Salomon, 1700-1761 (artist):::Creator::::::::::::; Corvinus, Johann August, 1683-1738 (engraver):::Contributor:::::::::::: (Johann Andreas Pfeffel)
Color engraving of the Leopoldstadt near Vienna